Learning to Embrace Nuclear Physics through Education - Avadanei, Camelia (AIP conference proceedings, 2010)
Due to its achievements, nuclear physics is more and more present in life of every member of the society. Its applications in the medical field and in nuclear energy, as well as the advanced research, always pushing the limits of science towards micro cosmos and macro cosmos, are subjects frequently presented in the media. In addition to their invaluable benefits, these achievements involve also particular rules to prevent potential risks. These risks are also underlined by the media, often being presented in an unfriendly manner. Specialists in nuclear physics are familiar with these problems complying with the specific rules in order to reduce risks at insignificant levels. The development of a specific field ('Radiation protection') defining norms and requirements for 'assuring the radiological safety of the workers, population and environment', and its dynamics represent a proof of a responsible attitude regarding nuclear safety. Dedicated international bodies and experts analyze and rigorously evaluate risks in order to draw the right ways of managing activity in the field. The improvement of the formal and informal education of public regarding the real risks of nuclear applications is very important in order to understand and better assimilate some general rules concerning the use of these techniques, as well as for their correct perception, leading to an increase of interest towards nuclear physics. This educational update can be started even from elementary school and continued in each stage of formal education in adapted forms. The task of informing general public is to be carried out mainly by specialists who, unlike 30-40 years ago, can rely on a much more efficient generation of communications' mean. Taking into account the lack of interest for nuclear, an attractive way of presenting the achievements and future possibilities of nuclear physics would contribute to youth orientation towards specific universities in order to become next generation of specialists in the field. Facing new challenges, society becomes aware of the fact that education represents the real solution to escalade them. Nuclear physics plays an important role in ensuring energetic resources for the near future and in reducing greenhouse effects. On the other hand, especially nuclear physics will permit to solve the enigma of universe birth. As in any other field, development involves continuous education and knowledge upgrading for all categories carrying out nuclear activities. For radiation protection workers and specialists, periodically refreshment courses are mandatory, in compliance with the national and international specific requirements.